2020
DOI: 10.5604/01.3001.0014.6225
|View full text |Cite
|
Sign up to set email alerts
|

The moderation effect of genderon the relationship between student alienation, engagement, and burnout

Abstract: Background: Burnout syndrome is a condition which can affect people in a variety of settings and in every period of life. Preliminary studies have focused on adults’ burnout related to occupational hazards. However, in recent years researchers have become increasingly interested in student burnout in the academic and school setting. Objective: The current study analyzed the moderation effect of gender on the association between student engagement, student alienation, and school burnout. Methods: 109 secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Similarly, poor school adjustment due to work overload and high levels of school-related stress and burnout may generate negative feelings toward school in adolescents, thus confirming the results and conclusions of Salmela-Aro and Upadyaya (2014) about the important role of school burnout for the later decrease in connectedness and sense of relatedness to school. Moreover, following the person-environment fit framework, when the school setting satisfies adolescents’ need for belongingness, students may handle best school-related stress and demands, reducing the risks of burnout (Eccles & Roeser, 2011; Tomaszek, 2020). Concurrently, when students face high levels of stress, cynicism, and exhaustion, they are less likely to experience positive feelings and a sense of attachment toward the school context and the people within it.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, poor school adjustment due to work overload and high levels of school-related stress and burnout may generate negative feelings toward school in adolescents, thus confirming the results and conclusions of Salmela-Aro and Upadyaya (2014) about the important role of school burnout for the later decrease in connectedness and sense of relatedness to school. Moreover, following the person-environment fit framework, when the school setting satisfies adolescents’ need for belongingness, students may handle best school-related stress and demands, reducing the risks of burnout (Eccles & Roeser, 2011; Tomaszek, 2020). Concurrently, when students face high levels of stress, cynicism, and exhaustion, they are less likely to experience positive feelings and a sense of attachment toward the school context and the people within it.…”
Section: Discussionmentioning
confidence: 99%
“…Hazel et al (2014) reported that this scale has good reliability. Tomaszek (2020) report that the Cronbach's alpha of the SSEM ranges from 0.76 to 0.84 for the factors of engagement and is 0.89 for the overall measure of engagement.…”
Section: Methodsmentioning
confidence: 99%
“…This state generates excessive and intense involvement in professional (or educational) activities, exceeding their energy resources [ 10 ]. Burnout syndrome, also referred to in the literature as exhaustion syndrome (analogous to burnout syndrome), consists of three aspects according to the most popular structural approach: a state of chronic energy exhaustion (referred to as emotional burnout or simply burnout), a cynical attitude (referred to as depersonalization), and a sense of dissatisfaction with personal achievements (referred to as a sense of inadequacy) [ 11 , 12 ]. In 2011, Aypay [ 13 ] analyzed the symptoms of burnout syndrome among young people and revealed that this phenomenon has a seven-element structure: learning exhaustion, parental pressure burnout, loss of interest in school, homework burnout, teacher pressure burnout, need for rest and free time, and a feeling of ineptitude at school.…”
Section: Introductionmentioning
confidence: 99%
“…In 2011, Aypay [ 13 ] analyzed the symptoms of burnout syndrome among young people and revealed that this phenomenon has a seven-element structure: learning exhaustion, parental pressure burnout, loss of interest in school, homework burnout, teacher pressure burnout, need for rest and free time, and a feeling of ineptitude at school. School burnout is significantly related with interpersonal relationships, which makes students more susceptible to depression and puts them at higher risk of developing suicidal tendencies [ 12 , 14 ].…”
Section: Introductionmentioning
confidence: 99%